Promoting equity through teacher practices: A scoping review on transformative social-emotional learning - Yadati, Nymisha; Thomas, Benny; Rajan, Santhosh Kareepadath (Issues in educational research, 2025)
Literature on teachers' transformative social-emotional learning (TSEL) is emerging and focuses on improving teachers' competency in delivering and implementing equity-focused SEL among students. Our study is a scoping review aiming to understand the characteristics of existing literature regarding teachers' TSEL, identify gaps, and discuss future research directions. It follows JBI guidelines for a scoping review and the PRISMA-ScR method for screening the literature. A systematic search was conducted in eight databases, and eleven studies were identified. Our findings report the characteristics of the studies and explain related concepts. We found that teachers need to be engaged in transformative SEL education to implement TSEL among students and build healthy teacher-student bonds. Teachers need to incorporate culturally relevant pedagogies in SEL to cater for the needs of students from diverse communities. Stretching was identified as a strategy to integrate social justice issues into traditional SEL practices to make social-emotional learning transformative.